Texas Willie [compact disc] - Nelson, Willie, 1933- (Sunset Blvd Records, 2021)
Willie Nelson first established himself as part of a new generation of progressive country songwriters in the early '60s. Here are the obscure and rarely heard demo recordings he made prior to signing to Liberty and before RCA.